Governance Failure in the City of Johannesburg Amid the Forthcoming 2026 Local Government Elections - John Mamokhere (Universitas Airlangga, 2026)
Abstract The proposed Turnaround Strategy 2024 (TAS24) for the City of Johannesburg reflects the municipality’s persistent governance challenges, characterized by political instability, administrative inefficiency, financial mismanagement, and declining service delivery. These challenges have significant implications for public trust and electoral behaviour ahead of the 2026 local government elections. This study explores the underlying causes, indicators, and implications of governance failure in the City of Johannesburg. Guided by the Dead Horse Theory, the study employs a qualitative desktop research approach, drawing on Auditor-General reports, policy documents, government publications, and scholarly literature to analyze patterns of governance dysfunction within the municipality. The findings reveal that governance failure is driven by the interconnected effects of unstable coalition politics, frequent leadership changes, including nine mayors in less than ten years, weak administrative capacity, and inadequate financial oversight. These factors have contributed to the deterioration of municipal infrastructure, unreliable basic services, and growing public dissatisfaction. The study further demonstrates how governance failures shape citizens’ perceptions of local government performance and may influence voter behaviour and political accountability in local elections. It contributes to governance and local election scholarship by illustrating the relationship between municipal governance performance and democratic legitimacy in a metropolitan context. The study recommends the professionalization of municipal administration, stronger accountability and financial oversight mechanisms, improved service delivery management, and enhanced citizen participation to restore public confidence and governance stability. These measures are essential for improving municipal performance and strengthening democratic governance in Johannesburg. Keywords: coalition politics; governance; political instability; local government elections; service delivery; protests